AI-ASSISTED PODCAST CREATION IN EFL LEARNING: ENHANCING SPEAKING FLUENCY AND REDUCING FOREIGN LANGUAGE ANXIETY AMONG GEN Z LEARNERS - Suci Amaliah; Ika Yuli Wahyuni; Murdia Murdia; Areski Wahid (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
In the era of artificial intelligence (AI)–driven education, integrating emerging technologies into English as a Foreign Language (EFL) pedagogy remains a critical challenge, particularly in balancing linguistic improvement and affective well-being. Despite growing research on digital tools, few studies have empirically examined how AI-assisted podcast creation can simultaneously enhance speaking fluency and alleviate foreign language anxiety (FLA) among Gen Z learners. This study employed a mixed-method design to investigate these dual outcomes among 120 undergraduate EFL students at Universitas Negeri Makassar. Participants were divided into an experimental and a control group, with the former engaging in AI-enhanced podcast projects using Podcastle and ElevenLabs, while the latter conducted traditional oral presentations. Quantitative data from pre- and post-tests and the Foreign Language Classroom Anxiety Scale (FLCAS) were triangulated with qualitative data from reflective journals and focus group interviews. Statistical analyses revealed significant gains in speaking fluency (p < .001, Cohen’s d = 0.85) and a substantial reduction in anxiety levels (p < .01). Thematic analysis further indicated that AI-assisted podcasting fostered greater learner autonomy, digital confidence, and emotional regulation. These findings substantiate the pedagogical value of AI-driven multimodal production tasks and provide an evidence-based framework for integrating technology, fostering affective learning, and developing communicative competence in EFL contexts. The study underscores the transformative role of AI in reshaping 21st-century language education and provides a timely contribution to the global discourse on human–AI collaboration in learning.